Multipotent Adult Progenitor Cells Suppress T Cell Activation in In Vivo Models of Homeostatic Proliferation in a Prostaglandin E2-Dependent Manner - Carty, Fiona; Corbett, Jennifer M.; Cunha, João Paulo M. C. M.; Reading, James L.; Tree, Timothy I. M.; Ting, Anthony E.; Stubblefield, Samantha R.; English, Karen (Frontiers in Immunology, 2018)
Lymphodepletion strategies are used in the setting of transplantation (including bone marrow, haematopoietic cell and solid organ) to create space or to prevent allograft rejection and graft versus host disease (GvHD). Following lymphodepletion, there is an excess of IL-7 available and T cells that escape depletion respond to this cytokine undergoing accelerated proliferation. Moreover, this environment promotes the skew of T cells to a Th1 pro-inflammatory phenotype. Existing immunosuppressive regimens fail to control this homeostatic proliferative (HP) response, and thus the development of strategies to successfully control HP while sparing T cell reconstitution (providing a functioning immune system) represents a significant unmet need in patients requiring lymphodepletion. Multipotent adult progenitor cells (MAPC) have the capacity to control T cell proliferation and Th1 cytokine production. Herein, this study shows that MAPC cells suppressed anti-thymocyte globulin induced cytokine production but spared T cell reconstitution in a pre-clinical model of lymphodepletion. Importantly, MAPC cells administered intraperitoneally were efficacious in suppressing IFN- production and in promoting the expansion of regulatory T cells in the lymph nodes. MAPC cells administered intraperitoneally accumulated in the omentum but were not present in the spleen suggesting a role for soluble factors. MAPC cells suppressed lymphopenia induced cytokine production in a PGE2 dependent manner. This study suggests that MAPC cell therapy may be useful as a novel strategy to target lymphopenia induced pathogenic T cell responses in lymphodepleted patients.